Critical literacy through Information and Communication Technologies in the primary educational systems of Spain and Switzerland: A comparative study based on the example of WebQuests - Mathioudaki, Konstantina; Gkaravelas, Konstantinos (International Journal of Educational Innovation and Research, 2023)
In this present paper, a comparative study between the Spanish and Swiss primary educational systems took place, investigating whether WebQuests are used in the foreign language lesson for the instruction of critical literacy in multilingual environments. The modern learning environment requires student-centred teaching, with new technologies creating ideal learning conditions which, although they carry many risks, have advantages over traditional ones, creating a lively learning and collaborative environment. In the case of WebQuests, searching for information on the internet ceases to be an arduous process, since it is guided. In addition, it enhances and promotes reflection, critical thinking, creativity, discovery and presentation of new information, delving into real-life issues and situations which are key elements of critical literacy.